(untitled) (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Hapsari L, Kennedy J, Lestari DA, Masrum A, Lestarini W.2017. Ethnobotanical survey of bananas (Musaceae) in six districts of East Java, Indonesia. Biodiversitas 18: 160-174. Ethnobotanical survey of bananas was conducted in six districts of East Java, Indonesia i.e. Pasuruan, Probolinggo, Banyuwangi, Lumajang, Jember and Malang during 2012-2015. Seventy-nine local cultivar names were recorded in the six districts, including local Javanese names and some possible synonyms among the cultivars. Four genomic groups are represented: AA (13), AAA (16), AAB (24) and ABB (16); 10 specimens are uncertain AA/AAA/AAB. Banana cultivar names given by local communities mostly reflect distinct morphological or perceptual characteristics, as well as uses, although some of the names do not refer to appearance or anything at all. Some cultivars were restricted to particular regions. Bananas play important roles in East Javanese socio-economic and cultural life. All parts of the plant are used: for food, fodder, domestic materials, fibers, shelters, ornamentals, medicines, in rituals and ceremonial events and other miscellaneous uses. Banana plants have deep philosophical meaning; their characteristics are associated with the process of life and provide lessons on life ethics. Conservation of local banana cultivars is needed in the face of negative impacts of commercialism. In-situ/on-farm conservation of bananas is a suitable strategy. Conserving the diverse species and varieties of bananas is necessary to maintain their adaptability and resilience to resist biotic and abiotic stresses. Key words: banana, diversity, East Java, ethnobotany, Musa, ritual, uses